Availability and Diversity of Health Human Resources at Public Health Center (PHC) In Indonesia - Ayu Prasetyowati; Meliana Handayani (Humanistic Network for Science and Technology (HNST), 2018)
Health human resource is a strategic issue in the implementation of government’s primary health services in Indonesia. The problem of distribution of both the number and diversity of health human resources in Indonesia is still a problem, making it more difficult to achieve the national health development goals equally.This was a descriptive research with literature review approach. Study literature was conducted by reviewing the regulation in Indonesia, journal and other articles related to health human resource problem. Distribution of health human resources at Public Health Center (PHC) in Indonesia was not evenly distributed. Some of PHC have health workers exceed the standards, while others were shortage of health personnel. In addition, the problem of synchronization of health human resources data derived from documents issued by the central and local governments was still a problem in Indonesia. It is necessary to formulate the planning of health human resource needs in each primary health care, this is due to differences in characteristics and needs. Central and local government work together to solve health human resource problems in Indonesia both on availability, diversity and quality of health human resources. Keywords: Availability, Diversity of types, Health human resources.